2021
DOI: 10.1021/jacs.1c03428
|View full text |Cite
|
Sign up to set email alerts
|

Surface Hydrides on Fe2P Electrocatalyst Reduce CO2 at Low Overpotential: Steering Selectivity to Ethylene Glycol

Abstract: Development of efficient electrocatalysts for the CO2 reduction reaction (CO2RR) to multicarbon products has been constrained by high overpotentials and poor selectivity. Here, we introduce iron phosphide (Fe2P) as an earth-abundant catalyst for the CO2RR to mainly C2–C4 products with a total CO2RR Faradaic efficiency of 53% at 0 V vs RHE. Carbon product selectivity is tuned in favor of ethylene glycol formation with increasing negative bias at the expense of C3–C4 products. Both Grand Canonical-DFT (GC-DFT) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 65 publications
4
57
0
Order By: Relevance
“…Thus, Cu sits at the sweet spot because it exhibits strong enough CO binding, but thermoneutral H adsorption. Finally, oxygen binding energy was proposed as a descriptor for alcohol vs hydrocarbon competition, and this prediction was later confirmed by experimental reports on eCO 2 R to methanol or methane on Au, Cu, and Ag electrodes. ,, As a crucial remark, we highlight that the above-mentioned descriptors are specifically tailored to single metals, thus alloys or oxide-derived materials may have completely different reactivity, see, for instance, eCO 2 R to C 2 products (specifically ethylene glycol) on Fe 2 P and nickel oxygenates …”
Section: Co2 Reduction On Crystalline Materialssupporting
confidence: 64%
“…Thus, Cu sits at the sweet spot because it exhibits strong enough CO binding, but thermoneutral H adsorption. Finally, oxygen binding energy was proposed as a descriptor for alcohol vs hydrocarbon competition, and this prediction was later confirmed by experimental reports on eCO 2 R to methanol or methane on Au, Cu, and Ag electrodes. ,, As a crucial remark, we highlight that the above-mentioned descriptors are specifically tailored to single metals, thus alloys or oxide-derived materials may have completely different reactivity, see, for instance, eCO 2 R to C 2 products (specifically ethylene glycol) on Fe 2 P and nickel oxygenates …”
Section: Co2 Reduction On Crystalline Materialssupporting
confidence: 64%
“…Dismukes and his team investigated the process of CO 2 RR on the surface of Fe 2 P at low potential by Grand Canonical-DFT (GC-DFT). [98] The results of GC-DFT showed that *CO mainly formed ion hydrides at surface phosphorus atoms (H@P s ) and P-reconstructed Fe 3 hollow sites (H@P*) and *formate is the initial intermediate of surface phosphine hydride formation (Figure 4b). The more negative the applied potential was, the weaker the binding of these surface hydrides was, indicating the enhancement of HER and the transformation of multicarbon products (C 3 products or C 4 products) to C 2 products.…”
Section: Dft Calculations For Co 2 Rr Investigationmentioning
confidence: 99%
“…Reproduced with permission. [98] Copyright 2021, American Chemical Society. d) Summary of limiting potentials for the six most promising DACs.…”
Section: Dft Calculations For Nrr Investigationmentioning
confidence: 99%
“…This phenomenon has been used to rationalize electrochemical CO2 reduction on Fe2P and Ni2P nanocrystals, where it was proposed that in addition to creating local active site motifs for CO2 hydrogenation, the binary surface also dictates the selectivity between various multiple carbon products. 94,95 DFT studies have shown that C-C coupling on Ni2P via *HCOO self-condensation is exergonic due to the presence of many types of H-binding sites, which results in selectivity toward multicarbon products. 103 It may be intuitive to think that the many H-adsorption sites promote higher activity for HER; however, it instead provides facile hydrogenation of CO2 intermediates.…”
Section: The Role Of Adsorption Site Diversity In Reactions Beyond He...mentioning
confidence: 99%